2016
DOI: 10.1108/ilt-10-2015-0157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hexagonal boron nitride nanoparticles as an additive on the extreme pressure properties of engine oil

Abstract: About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services.Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 15 publications
(22 reference statements)
3
32
0
1
Order By: Relevance
“…For a lubricant containing h-BN nanoparticles, the friction coefficient is comparatively less at the corresponding loads. This is due to the stable film formation capability of the boron element present in the boron nitride nanoparticles (Abdullah et al 2016), which is also shown in Fig. 17b.…”
Section: Tribological Studiesmentioning
confidence: 69%
“…For a lubricant containing h-BN nanoparticles, the friction coefficient is comparatively less at the corresponding loads. This is due to the stable film formation capability of the boron element present in the boron nitride nanoparticles (Abdullah et al 2016), which is also shown in Fig. 17b.…”
Section: Tribological Studiesmentioning
confidence: 69%
“…However, the most extensive studies have been carried out with metal-containing nanomaterials, whose NPs contain, e.g., metals, their oxides, and sulfides [32][33][34]. Importantly, some of the nanomaterials studied are commercial products [35][36][37][38][39], but most studies are concerned with self-made NPs. Various chemical and physical methods are used to obtain NPs [40][41][42][43][44], and they continue to improve.…”
Section: Introductionmentioning
confidence: 99%
“…On this subject, Gulzar et al [5] prepared a large-scale literature review that examined the tribological properties of nanoparticles added to lubricants. In this review, the effect of nanoparticles on lubricity was revealed by four different lubrication mechanisms such as a ball bearing effect [6][7][8], protective film formation [9][10][11], mending effect [12], and polishing effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…Herrmann et al [7] determined the cooling and lubrication properties of vegetable oils using the grinding test. Abdullah et al [8] determined the properties of nanoparticle-added lubricants under high pressure using the four-ball method. In addition, methods such as ring compression [17,18] and pin on disk [5,19] were used to determine the friction coefficient and lubricant effect in forming processes.…”
Section: Introductionmentioning
confidence: 99%